The influence of service quality, physician communication, and patient trust on outpatient satisfaction in hospitals - Syahriza Naufal Kingwijati; Jessica Sharma; Sinta Poernomo; Florida Bhoki (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Patient satisfaction is a key indicator of hospital service quality and is influenced by service quality, doctor–patient communication, and patient trust, particularly in outpatient care. Purpose: To analyze the effects of service quality, doctor communication, and patient trust on outpatient satisfaction based on patients' experiences in hospitals. Method: Quantitative cross-sectional study involved 182 participants who had used outpatient services and were asked to rate one hospital they had previously visited. Data were collected using a Likert-scale questionnaire measuring service quality, doctor communication, patient trust, and patient satisfaction, and were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1 through evaluation of the measurement and structural models. Results: The model yielded an R² of 0.711 for patient satisfaction, a Q² of 0.449, and a Goodness of Fit of 0.679. Service quality (β=0.458; p<0.001), doctor communication (β=0.304; p=0.001), and patient trust (β=0.175; p=0.039) had positive and statistically significant effects on patient satisfaction, with service quality being the most dominant predictor. Conclusion: These findings highlight the importance of improving service quality, strengthening doctor, patient communication, and fostering patient trust to enhance patient satisfaction.